2016
DOI: 10.3892/br.2016.829
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 in development and differentiation

Abstract: Among the human kinomes, protein kinase CK2 (formerly termed casein kinase II) is considered to be essential, as it is implicated in the regulation of various cellular processes. Experiments with pharmacological inhibitors of the kinase activity of CK2 provide evidence that CK2 is essential for development and differentiation. Therefore, the present review addresses the role of CK2 during embryogenesis, neuronal, adipogenic, osteogenic and myogenic differentiation in established model cell lines, and in embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 92 publications
1
70
0
Order By: Relevance
“…CK2 is involved in fundamental cellular processes (1,10), and the dysregulation of its signaling is associated with a wide spectrum of human diseases (2,3). CK2 is also implicated in cell differentiation in various tissues, including skeletal muscle (1,10,11). Skeletal muscle differentiation is an irreversible and tightly orchestrated process, initiated by the activity of key transcription factors of the myogenic regulatory factor (MRF) family, such as myogenic differentiation 1 (MyoD) and myogenic factor 5 (Myf-5).…”
mentioning
confidence: 99%
“…CK2 is involved in fundamental cellular processes (1,10), and the dysregulation of its signaling is associated with a wide spectrum of human diseases (2,3). CK2 is also implicated in cell differentiation in various tissues, including skeletal muscle (1,10,11). Skeletal muscle differentiation is an irreversible and tightly orchestrated process, initiated by the activity of key transcription factors of the myogenic regulatory factor (MRF) family, such as myogenic differentiation 1 (MyoD) and myogenic factor 5 (Myf-5).…”
mentioning
confidence: 99%
“…In vitro cell experiments have shown that CK2 inhibition results in cell cycle blockage and death [36][37][38][39]. Thus, CK2 has been associated with proliferation, lineage determination and differentiation of various tissues, including skeletal muscle [40].Pax7 locus [17]. In addition, phosphorylation of Brg1 by CK2 correlated with the subunit composition of the mSWI/SNF enzyme complex and its sub-nuclear localization [17].Here we report novel findings about Brg1 phosphorylation by CK2.…”
mentioning
confidence: 99%
“…In vitro cell experiments have shown that CK2 inhibition results in cell cycle blockage and death [36][37][38][39]. Thus, CK2 has been associated with proliferation, lineage determination and differentiation of various tissues, including skeletal muscle [40].…”
mentioning
confidence: 99%
“…In yeast these units can each be of two types and are named a1, a2, b1 39 and b2 (Padmanabha et al, 1990) while several other fungi, including M. oryzae, only contain one CKa 40 (Zhang et al, 2019). CK2 have been shown to phosphorylates a large number of proteins (Meggio and 41 Pinna, 2003;Ahmad et al, 2008;Götz and Montenarh, 2016) and seems involved in many cellular 42 processes (Götz and Montenarh, 2016). Interestingly, intrinsically highly disordered SRP40 protein in 43 yeast (homologous to Nopp140; Insect, Drosophila and Nolc1;Mammal, Human) has been shown to 44 become phosphorylated to varying degrees by CK2 with effects on the SRP40 conformation, binding, 45 and aggregation properties with further effects on the diverse functions of the protein (Tantos et al, 46 2013; Na et al, 2018).…”
mentioning
confidence: 99%